Nanowire-Haired Inorganic Membranes with Superhydrophilicity and Underwater Ultralow Adhesive Superoleophobicity for High-Efficiency Oil/Water Separation - Zhang, Feng; Zhang, Wen Bin; Shi, Zhun; Wang, Dong; Jin, Jian; Jiang, Lei (Advanced materials (Weinheim), 2013)
A novel all‐inorganic Cu(OH)2 nanowire‐haired membrane with superhydrophilicity and underwater ultralow adhesive superoleophobicity is fabricated by a facile surface oxidation of copper mesh that allows effective separation of both immiscible oil/water mixtures and oil‐in‐water emulsions solely driven by gravity, with extremely high separation efficiency. The all‐inorganic membrane exhibits superior solvent and alkaline resistance and antifouling property compared to organic‐based membranes.